Neoadjuvant chemotherapy response influences outcomes in non-colorectal, non-neuroendocrine liver metastases. Issue 12 (12th June 2018) - Lucchese, A M; Kalil, A N; Ruiz, A; Karam, V; Ciacio, O; Pittau, G; Castaing, D; Cherqui, D; Sa Cunha, A; Vibert, E; Adam, R
Abstract: Background: Indications for surgical resection of non-colorectal, non-neuroendocrine (NCNNE) liver metastases are unclear. This study analysed the influence of response to neoadjuvant chemotherapy and the presence of extrahepatic disease (EHD) on outcomes. Methods: Patients who underwent hepatic resection for NCNNE liver metastases and who received neoadjuvant chemotherapy at a single centre between 1982 and 2016 were analysed retrospectively. Patients were classified as having no EHD, controlled EHD or non-controlled EHD. Results: Hepatic resection was performed in 199 patients (81·2 per cent) after partial or complete response to chemotherapy or disease stabilization, and 46 patients (18·8 per cent) after tumour progression. Patients with progressive disease after chemotherapy had worse overall survival than those without (23 versus 50·4 per cent at 5 years; P = 0·004). Median survival was 63·6 (range 31·1–94·8) months for patients without EHD, 34·8 (19·2–49·2) months for those with controlled EHD and 7·2 (1·2–13·2) months for patients with non-controlled EHD ( P = 0·004). In multivariable analysis, EHD ( P = 0·004), response to chemotherapy ( P = 0·004) and resection margins ( P = 0·002) were all independent predictors of overall survival, regardless of primary tumour site. Conclusion: The prognosis of patients with NCNNE liver metastases is influenced by preoperative chemotherapy and resectability. Abstract : Multimodal therapy works